UPAYA MENINGKATKAN PEMAHAMAN SISWA TERKAIT MAKANAN HALAL DAN BAIK DENGAN IMPLEMENTASI PEMBELAJARAN BERBASIS PROYEK - aman aman (MGMP PAI Jawa Barat, 2023)
This study is a qualitative study, which was carried out in the form of Classroom Action Research (PTK) with 37 students participating, and the researcher himself acting as a participant observer. This research aims to find out how the implementation of a project-based learning model can increase students' understanding of halal and nutritious food in studying PAI in Class VII-B at SMP Negeri 4 Cirebon. The research carried out in two cycles used observation and document review as data collection techniques. The findings were then analyzed qualitatively based on the theories put forward in the research. The findings of this research are that the implementation of the Project Based learning model is able to improve student learning outcomes in participating in PAI learning activities in Class VII-B of SMP Negeri 4 Cirebon. This is proven by the fact that there is a very significant increase in learning outcomes between Cycles I and II regarding the ability to understand what types of food are halal and good. Maximum motivation and material enrichment can increase students' self-confidence to be involved and motivated in learning activities. However, hard work is required for teachers who implement the Project Based learning model considering that teachers must be able to direct and provide maximum motivation to students. Adequate practice is very necessary for students to be able to draw well. Teachers who implement the Project Based learning model must have adequate understanding regarding the use of learning media. This research was only carried out for a short time and on a limited scale, so further research regarding the themes mentioned above needs to be carried out to obtain much more satisfactory results.